In Vitro Production of Mouse Mammary Tumor Virus in a Mouse Mammary Tumor Ascites Line - Keydar, Jafa (1973)
An ascites line derived from a spontaneous mouse mammary carcinoma produces, on explantation and cultivation in vitro, large amounts of oncornavirus particles. The biochemical, biophysical, and electron microscopic characteristics of the virions are described. Molecular hybridization and immunological methods identify these virions as mouse mammary tumor virus.